Cooperatives for staple crop marketing: Evidence from Ethiopia - Bernard, Tanguy; Spielman, David J.; Taffesse, Alemayehu Seyoum; Gabre-Madhin, Eleni Zaude (International Food Policy Research Institute, 2010)
Rural producer organizations, such as farmers' organizations or rural cooperatives, offer a means for smallholder farmers in developing countries to sell their crops commercially. They hold particular promise for Sub-Saharan Africa, where small-scale farming is the primary livelihood but commercialization of foodcrops is very limited. Using the experience of smallholders in Ethiopia as a case study, this research monograph identifies the benefits of rural producer organizations for small farmers, as well as the conditions under which such organizations most successfully promote smallholder commercialization. The evidence from Ethiopia indicates that they do increase farmers' profits from crop sales, but that the beneficiaries do not tend to be the poorest smallholders. Moreover, a rural producer organization's marketing effectiveness is precarious: it can easily diminish if the number or diversity of its members increases or if it provides more nonmarketing services. The authors conclude that these organizations have a role to play in the agricultural development of Sub-Saharan Africa, but that role should be complemented by other programs that directly target the poorest farmers. Further, the effectiveness of rural producer organizations should be preserved by allowing them to follow their own agendas rather than being encouraged to take on nonmarketing activities. The assessment of rural producer organizations presented in this monograph should be a valuable resource for policymakers and researchers concerned with economic development and poverty reduction in Sub-Saharan Africa.